2022
DOI: 10.1108/jsm-01-2022-0035
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of facial recognition payment service: a mixed method approach

Abstract: Purpose Sellers view facial recognition mobile payment services (FRMPS) as a convenient and cost-saving way to receive immediate payments from customers. For consumers, however, these biometric identification technologies raise issues of usability as well as privacy, so FRMPS are not always preferable. This study uses the stressor–strain–outcome (S–S–O) framework to illuminate the underlying mechanism of FRMPS resistance, thereby addressing the paucity of research on users' negative attitudes toward FRMPS. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 86 publications
2
12
0
Order By: Relevance
“…Consistent with the previous study (Lee and pan, 2022), in other contexts, results suggested that technostress plays an essential role in framing customers’ resistance intention. If customers perceive barriers to using mobile bookkeeping applications, they tend to trigger technostress among users and ultimately represent resistance to the platform.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with the previous study (Lee and pan, 2022), in other contexts, results suggested that technostress plays an essential role in framing customers’ resistance intention. If customers perceive barriers to using mobile bookkeeping applications, they tend to trigger technostress among users and ultimately represent resistance to the platform.…”
Section: Discussionsupporting
confidence: 90%
“…Thirdly, in addition to the barriers, the findings indicate that technostress and self-efficacy have significantly affected user resistance. The mediating effect of technostress and the moderating effect of self-efficacy has been rarely examined in the literature (Lee and Pan, 2022; Henkens et al , 2021). Therefore, the present study contributes significantly to the literature by providing new variables used as mediators and moderators in the mobile bookkeeping application resistance context.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations